Tax mimicking among local governments : some evidence from Spanish municipalities - Delgado, Francisco J. (2018)
The aim of this paper is to study the spatial patterns in the Spanish local tax system. The three most relevant taxes are analyzed: the property tax, the motor vehicle tax and the building activities tax, which jointly represent 80% of the tax revenue at local level in Spain. Using spatial econometrics procedures, three alternative weight specifications to define competitors are explored: contiguity, distance and a combination of economic and geographical characteristics. After carrying out an exploratory spatial analysis, the results of the estimation of spatial lag and spatial error models confirm positive spatial- autocorrelation for the property tax and the building activities tax, with an order of magnitude between 0.3 and 0.5. On the contrary, the motor vehicle tax does not exhibit a significant spatial pattern.